Effect of Organic Zinc (Zinc glycinate) and Probiotic (Saccharomyces cerevisiae) Supplementation on Serum Biochemical Profile, Oxidative Stress Indices and Carcass characteristics in Broiler Chickens - Sahu, Dayamand; Kumari, Kiran; Archana; Pal, Prasanna; Gendley, M. K. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during May–June, 2018 at the Poultry Shed of the Department of Animal Nutrition, College of Veterinary Science and Animal Husbandry, Anjora, Durg, Chhattisgarh, India to evaluate the effect of dietary supplementation of organic zinc (zinc glycinate) and probiotic Saccharomyces cerevisiae on serum biochemical constituents, oxidative stress indices and carcass characteristics in broiler chickens. 180 day old chicks were randomly allocated into 2×3 factorial scheme following 90 chicks in each group and each group was again subdivided into three subgroups having 3 replicates of 10 birds in each subgroup. Six type of diets were formulated: diet T1, T2 and T3 contained inorganic source of zinc (ZnSO4) with 0, 0.5, 1% of probiotic (S. cerevisiae) respectively and diet T4, T5 and T6 contained organic source of zinc (Zn-glycinate) with 0, 0.5, 1% of probiotic (S. cerevisiae) respectively. Dietary supplementation of organic zinc (zinc glycinate) with probiotic Saccharomyces cerevisiae improved serum high density lipoprotein cholesterol, reduced glucose concentration, and enhanced antioxidant status in broiler chickens. Lipid peroxidation was lowered, while reduced glutathione levels increased, indicating strengthened antioxidant defence. Other biochemical parameters remained unaffected. It was concluded that dietary supplementation of organic zinc with S. cerevisiae improved overall haematological status, thereby mitigating oxidative stress in broiler chickens.